#TITLE_ALTERNATIVE# - GANJAR ZATNIKA (NIM : 13707013); Dosen Pembimbing : Dr. Ir. Slameto Wiryolukito ; Dr. Ir. Her, GIAN
The development of oil and gas exploration toward sour service environment encourages the improvement of line pipe and hot rolled coil (HRC) to have hydrogen induced cracking (HIC) resistance. HIC testing on the line pipe has been widely applied, but the HIC-resistance of HRC material has not been widely studied. In fact, the HIC-resistance of line pipe is very determined by properties and production control of HRC. Moreover, HRC materials are often meet the problem of plastic strain or a notch on the manufacturing, fabrication, and during lay-up sour service pipeline. Therefore, HIC testing on both of as-received HRC material and plastic strained or notched HRC material is necessary to know HIC-resistance in those condition. Material characterization prior to HIC testing is also needed to know the properties that influence HIC-resistance. HIC tests were conducted on both parallel and perpendicular specimen to rolling direction (RD) orientation of as-received and plastic strained HRC as raw material of API 5L X-52. The applied plastic strains were 5%, 10%, and 15%. HIC test was also conducted on parallel specimen orientation of notched HRC material. The notch orientations are parallel and perpendicular to RD. HIC tests are based on NACE TM0284-2003 with solution A for 96 hours. Chemical composition test, tensile test, hardness tests, and metallography has been done for characterize the HRC material before test. Then, evaluation of HIC test specimens has been completed by using visual observation, dye penetrant testing, metallography, and scanning electron microscopy. Characterizations of as-received material show that HRC is thermomechanical treated-HSLA with microalloy ferrite-pearlite and/or weathering steel class. It is suitable as raw material of API 5L X-52MS due to chemical composition, tensile, and hardness properties. HIC testing was conducted as per NACE TM0284-2003. The result are both of orientations of as-received HRC material is resistant to HIC due to Cu alloying, high ductility and toughness, high cleanness, and very fine polygonal ferrite microstructure (ASTM 12). HRC material which parallel to RD with plastic strain up to 15% and HRC material which perpendicular to RD with plastic strain up to 10% are resistant toward HIC. But, HIC crack occurs on 15%-plastic strained-HRC material which perpendicular to RD with CSR, CLR, and, CTR respectively 1,81%, 21,71%, and 8,43%. The HIC crack may be caused by uneven plastic deformation and inclusion indication which are detected in the crack surface. Meanwhile, HRC material which has notches with depth, width, and root radius respectively 589-980 μm ; 1152-1934 μm; and 139-222 μm is resistant to HIC.